Altered blood microbiome in patients with HCV-related Child-Pugh class B cirrhosis - Oscar Brochado-Kith; Marta Rava; Juan Berenguer; Juan González-García; David Rojo; Cristina Díez; Victor Hontañon; Ana Virseda-Berdices; Luis Ibañez-Samaniego; Elba Llop-Herrera; Antonio Olveira; Leire Pérez-Latorre; et al. (Elsevier, 2024)
Background: Altered bacterial translocation is associated with changes in hepatic function and the progression from compensated to decompensated cirrhosis. Child-Turcotte-Pugh (CTP) score is an essential indicator of liver severity. Thus, we aimed to study differences in the blood microbiome together with metabolome profile between HCV-infected patients with CTP class B (CTP-B, significant functional compromise) and patients with CTP class A (CTP-A, well-compensated cirrhosis). Methods: We conducted a cross-sectional study in patients with advanced HCV-related cirrhosis (n = 88) stratified by CTP-B and CTP-A. Bacterial 16S rRNA sequencing was sequenced by MiSeq Illumina technology and non-targeted metabolomics was performed by GC-MS and LC-MS ESI+ and ESI- to complement the analysis. Results: Patients with CTP-B had lower levels of richness (Chao1), and alpha diversity (Shannon and Simpson indexes) at phylum level than patients with CTP-A. Likewise, we observed significant differences in beta diversity between groups at phylum, class, and order levels, showing lower diversity in patients with CTP-B. Higher relative abundance of Proteobacteria (p = 0.012), Alphaproteobacteria (p = 0.005), Sphingomonadales (p = 0.012) and Sphingomonadaceae (p = 0.016) were significantly associated with CTP-B. The phylum Proteobacteria was positively correlated with ethanolamine and oleic acid (p = 0.005 and p = 0.004, respectively) and negatively with p-cresol (p = 0.006). In addition, the order Sphingomonadales and the family Sphingomonadaceae was also negatively correlated with p-cresol (p = 0.001 and p = 0.001). Conclusions: Blood microbial diversity was significantly decreased in patients with CTP-B, who presented an enrichment of Proteobacteria, Alphaproteobacteria, Sphingomonadales and Sphingomonadaceae compared to patients with CTP-A.